Characterization and cytotoxic activity on glial cells of alkaloid-enriched extracts from pods of the plants Prosopis flexuosa and Prosopis nigra (Fabaceae) - Cholich, Luciana Andrea; Pistán, María Elena; Torres, Ana María; Ortega, Hugo Héctor; Gardner, Dale R.; Bustillo, Soledad (Revista de Biología Tropical, 2021)
Introduction: Prosopis spp. pods have shown to be a potential source of protein and energy in livestock. However, prolonged ingestion of some of these species produces neurological symptoms in ruminants. Objective: In the present study, the alkaloid content and the in vitro neurotoxic activity of alkaloid enriched-extracts from P. flexuosa and P. nigra pods were determined in order to elucidate the mechanism of animal poisoning caused by these species. Methods: The main alkaloids present in both extracts were analyzed by high performance liquid chromatography-high resolution mass spectrometry (HPLC-HRMS). The cytotoxic activity of Prosopis alkaloid enriched-extracts in primary mixed glial cell culture was assessed by phase contrast microscopy and using neutral red, and lactate dehydrogenase (LDH) activity assays. Results: Juliprosine and juliprosopine were identified in P. flexuosa pods, while the absence of these alkaloids in P. nigra was confirmed. Both extracts (5-30 μg/mL) induced in a dose dependent manner, morphological alterations, such as swelling, enlargement and detachment from the culture surface. Consistent with this, decrease in cell viability and release of LDH 48 hours after exposure, revealed that P. flexuosa pods was significantly more cytotoxic than P. nigra. Conclusions: The present study suggest that the cytotoxic effect displayed by both extracts are due to the alkaloid content. However, the presence of the alkaloids juliprosine and juliprosopine in P. flexuosa could explain the greater cytotoxicity on glial cells with respect to P. nigra that was not shown to contain these alkaloids.